(untitled) (Research, Society and Development, 2022)
Madness is a concept historically forged by sociocultural aspects which aim to stigmatize and pathologize those who live at the margin of the rational scientific ideal. In this context, art becomes an important instrument not only for therapeutic work, but also for valuing the subjectivity of these individuals allowing them to speak out. Therefore, the following study reflects upon how art can be a way of promoting mental health, amplifying the potential of well being of the users and its contribution to the process of deinstitualization. The specific objectives are: emphasize the process of inclusion of art in the mental health scope; highlight the possible effects of art in the psychism; mention possible modalities in art therapy; showcase the legislation and which therapeutic workshops can be offered by Psychosocial Care Centers (CAPS). Therewith, the methodology chosen was bibliographic and qualitative research. As a result, it was found that art is an important vehicle of communication, which detains a signiticative therapeutic role, being a treatment that goes against the manicomial logic. Having said that, it was concluded that there is a necessity of more studies in artherapy, aiming at the continuous process of construction of reflections and transformations in the assistencial, cultural and conceptual fields.